SHOWCASING THE DIRECTIVE ILLOCUTIONARY ACT FOUND IN THE MOVIE MISS PEREGRINE'S HOME FOR PECULIAR CHILDREN - Wayan Maystana Setianda; Putu Desi Anggerina Hikmaharyanti (Universitas Pamulang, 2023)
This study examines the concept of illocutionary force in John Searles' speech act theory, with a particular focus on the directive aspect of illocutionary acts. The research seeks to completely examine directive illocutionary actions in the film's language using the film